Experimental research in comparison with effects of 6% dextran 70 and 7.5 % naci combinations and blood administrations for treatment of dogs with acute heamorrhagic shock syndrome - M. Arıcan; E. Keskin; C. Ceylan; K. Yiğitarslan (Eurasian Journal of Veterinary Sciences)
In this study, effects of small volumes of blood and 7.5 % NaCI/ 6 % dextran administrations in dogs with induced haemorrahagic shocks induced experimentally were investigated. For this purpose totally 12 dogs were used as a material. The dogs were divided into 2 groups each of 6 dogs. Haemorrhagic shock was performed experimentally by taking arterial blood via cut down catheters. By this way the mean arterial pressure was reduced to 40 ± 5 mmHg. At the end of the hypotensive period, the dogs of the group 1 and 2 were treated by bolus injection of 5ml/ kg of blood and 7.5 % NaCI/ 6 % dextran respectively. The blood samples for the determination of blood gases analyses were taken before the experiment, at the end of hypotensive period and after treatment at 30th, 60th and 90th minutes and other parameters (heart rate, blood pressure, respiration rate and body temperature) were recorded. In the study, Group 1 (treated by bolus injection of blood), after the bolus injection, blood pressure at 30th, 60th and 90th mins. were increased compare to the hipotensive period, but, this increased was only important at the 90th min. (p<0.05). On the other hand, these increased were important at the 30th, 60th and 90th minutes in group 2. Significantly decreased levels of arterial HCO3 and pC02 were found (p<0.05). The decreased levels of hematocrit values were significant compared to the hipotensive period in group 2 (p<0.05). After treatment of hypertonic fluid in group 2, plasma Na+ levels were significantly increased compared to the hipotensive period. Consideration in the study that particularly small volumes of 7.5 % NaCI/ 6 % Dextran administration in case of haemorrahagic shock, can make advantages.